The imperfectionists : a novel - Rachman, Tom. (New York : The Dial Press, 2010)
This is all about the goings-on among the staff of an English-language newspaper in Rome.
Keywords: Reporters and reporting -- Fiction; Newspaper publishing -- Fiction; Newspaper editors -- Fiction; Rome (Italy) -- Fiction